(untitled) (Research, Society and Development, 2022)
Objective: To present and discuss research that analyzed the use of antidepressants in the gestational period and the effects found on the baby’s development as a consequence of its exposure to pharmacological principles. Methodology: A bibliographic survey of 82 original publications was carried out, using descriptors: Pregnancy; Antidepressants; Embryonic and Fetal Development, in the VHL, Lilacs, Medline, Pubmed, Scielo, Science Direct, Scopus and Web of Science databases. After applying the inclusion and exclusion criteria proposed in the search design, a total of 9 publications accepted for use in this review. Results and Discussion: The results obtained indicate that there is clinical evidence that the use of antidepressants during pregnancy causes several effects that will compromise the baby’s development, from the intrauterine period to the process of acquiring new skills in the initial period of life. However, the clinical picture of untreated depression (PDNT) in pregnant women has been associated with increased risks for miscarriages, premature births and low birth weight of babies. Research also reveals a significant presence in the high levels of cortisol in pregnant women, directly reflecting on fetal development and increased maternal irritability during the process. Final considerations: It was possible to show that using antidepressants in the gestational period is associated with risks for both the mother and the fetus, generating fetal development impairment such as: hypoglycemia, malformations related to the cardiovascular system, propensity to develop ASD, or other cognitive, behavioral and long-term, directly compromising the quality of life for both.